APPLICATION OF MICROSOFT OFFICE EXCEL-BASED GOODS INVENTORY SYSTEM APPLICATION AT CV TRIKARTA JAYA INDONESIA - Nuryadi; Syamsul Arifin (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This study aims to describe the application of VBA Excel application. Sources of data in this study are primary data and secondary data. Data collection techniques used are observation, documentation, and interviews. The research used documentary data instrument. The data analysis technique in this study used descriptive analysis. This study analyzes the merchandise inventory system based on Microsoft Office Excel 2010 at CV Trikarta Jaya Indonesia in 2021. The results of this study are depicted in graphical form which is the result of recapitulation of merchandise inventory stock. The graph presented shows that the merchandise inventory system using Microsoft Office Excel is more effective and efficient than the manual system.